A MORPHOLOGICAL ERRORS ANALYSIS IN DESCRIPTIVE TEXTS WRITTEN BY THE STUDENTS - Isnaeni Fitriana Aziz; Asfi Aniuranti; Yasinta Wulandari (Economics, Social, and Humanities Journal (Esochum), 2023)
This research aimed to find out the types of morphological errors in descriptive texts and the causes of the errors. The research type was error analysis research. The techniques of collecting the data were written test and documentation. The subject of this research was the first-grade students of SMK Ma’arif NU 2 Ajibarang. The data gathered were analyzed using several relevant theories. The data analysis revealed that there were six types of morphological error called third-person singular error, article error, omission of noun plural, additional of noun plural, inflectional error, and possessive case error. Furthermore, the possible causes of the errors were incomplete of rule restriction, ignorance of the rule restriction, interlingual error, and carelessness.